2019
DOI: 10.1017/s1751731118003622
|View full text |Cite
|
Sign up to set email alerts
|

Review: Insects and former foodstuffs for upgrading food waste biomasses/streams to feed ingredients for farm animals

Abstract: The increasing global need to find alternative protein/energy sources has triggered research in the field of non-conventional feed ingredients, with insects and former foodstuffs being the most promising. Insects contain high level of protein and fat, whereas former foodstuffs contain high energy in the form of carbohydrates and fats; therefore, both should be considered as promising alternative feed ingredients for livestock production. In addition to the nutritional value, they also represent a way by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 42 publications
4
86
0
Order By: Relevance
“…Shaping insect nutrient profile -The low level of some nutrients in insects could represent a limit in animal nutrition; however, it has been shown that the nutrient composition of insects is highly dependent on the rearing substrates Danieli et al 2019). For example, using substrates naturally containing polyunsaturated fatty acids (PUFA) or rich in minerals allow to obtain enriched insect-derived materials that are more suitable for feed purposes (Liland et al 2017;Cullere et al 2019;Koutsos et al 2019;Pinotti et al 2019). Thus, the insect nutrient profile can be modulated by appropriate dietary strategies, according to specific animal dietary requirements.…”
Section: Strengthsmentioning
confidence: 99%
See 4 more Smart Citations
“…Shaping insect nutrient profile -The low level of some nutrients in insects could represent a limit in animal nutrition; however, it has been shown that the nutrient composition of insects is highly dependent on the rearing substrates Danieli et al 2019). For example, using substrates naturally containing polyunsaturated fatty acids (PUFA) or rich in minerals allow to obtain enriched insect-derived materials that are more suitable for feed purposes (Liland et al 2017;Cullere et al 2019;Koutsos et al 2019;Pinotti et al 2019). Thus, the insect nutrient profile can be modulated by appropriate dietary strategies, according to specific animal dietary requirements.…”
Section: Strengthsmentioning
confidence: 99%
“…The same comment can be applied to minerals as some species have low levels of calcium or phosphorus. However, adequate nutritional intervention in insects can improve this feature (Liland et al 2017;Pinotti et al 2019).…”
Section: Weaknessesmentioning
confidence: 99%
See 3 more Smart Citations